DNA microsatellite analysis for tomato genetic differentiation - Miskoska-Milevska, Elizabeta; Popovski, Zoran; Dimitrievska, Blagica; Bandzo, Katerina (National Library of Serbia, 2015)
Commonly used method for determination of the genetic diversity among the populations is the test for genetic differentiation. DNA microsatellite markers are usually used to investigate the genetic structure of natural populations. The aim of this study was to evaluate the applicability of eight DNA microsatellite loci (LECH13, LE21085, LEMDDNa, LEEF1Aa, LELEUZIP, LE20592, TMS9 and LE2A11) in genetic differentiation of six morphologically different tomato varieties (var. grandifolium from subsp. cultum; var. cerasiforme - red and yellow, var. pruniforme and var. pyriforme from subsp. subspontaneum; and var. racemigerum from subsp. spontaneum). The fragment analyses was performed using Applied Biosystems DNA analyzer (ABI 3130) and GeneMapper® Software program. The data were analysed using the specific program Power Marker Software. The average number of detected alleles was 3,625. Also, the average PIC value for all 8 DNA microsatellites loci was 0,3571. The genetic differentiation test in the researched tomato subspecies showed minor differentiation for locus LELEUZIP (- 0,0009), modest differentiation for locus LECH13 (0,0896), locus LEMDDNa (0,0896) and locus LE21085 (0,0551) and major differentiation for locus LE2A11 (0,7633), locus LEEF1Aa (0,6167), locus TMS9 (0.4967) and locus LE20592 (0,4263). On the other hand, in the estimated tomato varieties, locus LE21085 (0,0297), locus LECH13 (0,0256) and locus LELEUZIP (0,0005) showed minor differentiation, locus LEMDDNa (0,1333) showed modest differentiation, while locus TMS9 (0,5929), locus LEEF1Aa (0,5006), locus LE2A11 (0,4013) and locus LE20592 (0,2606) showed major differentiation. The eight DNA microsatellite loci can be applicable solution for tomato genetic differentiation. The overall results suggest that these microsatellite loci could be used in further population genetic studies of tomatoes.
Keywords: DNA microsatellites, genetic differentiation, Lycopersicon esculentum, subspecies, varieties.